Attachment-related dimensions in the epigenetic era: A systematic review of the human research. (June 2021) - Craig, Francesco; Tenuta, Flaviana; Rizzato, Veronica; Costabile, Angela; Trabacca, Antonio; Montirosso, Rosario
Highlights: 13 studies of association between attachment and DNAm in human were identified. DNAm (OXTR, NR3C1, FKBP5, SLC6A4, HTR3A) is associated with attachment. DNAm and attachment might affect the children's social and emotional development. Clinical implications and future directions in epigenetics research are proposed. Abstract: In recent years, an increasing number of studies documented potential links between parental care and epigenetic mechanisms. The present systematic review focuses on the potential association and interrelationship between attachment-related dimensions and DNA methylation in human studies. We performed a literature review using electronic databases such as PubMed, Scopus, Web of Science, and EBSCOhost. Thirteen papers were included in the review. Findings support significant associations between attachment-related dimensions and epigenetic status in studies which considered different populations, age ranges, attachment measures and peripheral tissues. Although research in this area is still under investigation, available results suggest that DNA methylation associated with attachment-related dimensions might affect the development of stress regulation system and social-emotional capacities, thus contributing to the emerging phenotypic outcomes. However, identifying mediator and moderator effects in the interrelationship between these parameters was problematic owing to heterogeneous methodologies. Finally, we discuss clinical implications, unanswered questions, and future directions for human development in epigenetics research.